Cervical cancer: perception of peripheral health workers in Lucknow: a cross-sectional study - Ansari, Arshi; Agarwal, Monika; Singh, V. K.; Nutan, Kumari; Deo, Sujata (International Journal Of Community Medicine And Public Health, 2019)
Background: Cervical cancer is one of the most prevalent cancers among Indian women. Cervical cancer incidence reduces dramatically when effective screening programs linked with access to treatment are in place and are readily accessible. Peripheral health workers (PHWs) being frontline workers have a major influence on raising awareness among community about acceptability of available screening programmes. This study was thus conducted to assess the awareness of PHWs regarding risk factors, signs and symptoms, early detection and prevention for cervical cancer. Methods: A questionnaire-based study was conducted among 450 PHWs (ASHAs and BHWs). Information was collected regarding their bio-social characteristics, awareness about female cancers, risk factors, signs/symptoms, early detection methods and services available for screening and prevention of cervical cancer. Results: Awareness of different aspects of cervical cancer was found to be very low. Only eight per cent of the PHWs had good awareness score. BHWs obtained statistically significant better mean scores as compared to ASHAs. Few (7.6%) PHWs had received training for any type of female cancers. Only 17 per cent of the PHWs were aware of HPV vaccine availability and only 29 per cent from them could name the vaccine. Conclusions: Majority of the PHWs had poor awareness about cervical cancer and available screening facility in our health system. They had almost no idea of availability of free HPV vaccination at the Sampoorna clinics. This low level of awareness calls for regular training of PHWs on cervical cancer which would ultimately trickle down to the community.